Biopsy Needle Advancement during Bone Marrow Aspiration Increases Mesenchymal Stem Cell Concentration - Peters, Anne E.; Watts, Ashlee E. (Frontiers in Veterinary Science, 2016)
Point-of-care kits to concentrate bone marrow (BM) derived mesenchymal stem cells (MSCs) are used clinically in horses. A maximal number of MSCs per ml of marrow aspirated might be desired prior to use of a point-of-care system to concentrate MSCs. Our objective was to test a method to increase the number of MSCs per ml of marrow collected. We collected 2 BM aspirates using 2 different collection techniques from 12 horses. The first collection technique was to aspirate BM from a single site without advancement of the biopsy needle. The second collection technique was to aspirate marrow from multiple sites within the same sternal puncture by advancing the needle 5 mm 3 times for BM aspiration from 4 sites. Numbers of MSCs in collected BM were assessed by total nucleated cell count (TNCC) of BM after aspiration, total Colony-Forming-Unit-fibroblast (CFU-F) assay, and total MSC number at each culture passage. The BM aspiration technique of 4 needle advancements during BM aspiration resulted in higher initial nucleated cell counts, more CFU-Fs, and more MSCs at the first passage. There were no differences in the number of MSCs at later passages. Multiple advancements of the BM needle during BM aspiration resulted in increased MSC concentration at the time of BM collection. If a point-of-care kit is used to concentrate MSCs, multiple advancements may result in higher MSC numbers in the BM concentrate after preparation by the point-of-care kit. For culture expanded MSCs beyond the first cell passage, the difference is of questionable clinical relevance.